Ameloblastoma of the mandible: analysis of radiographic and histopathological features - Ranchod Sanjay (Journal of Oral Medicine and Oral Surgery, 2021)
Introduction: Ameloblastoma is the most common benign tumour of odontogenic origin in Africa and presents five times more in the mandible than the maxilla. The presentation of ameloblastoma in the mandible is unique due to its anatomical variation and hence the aim of this study was to analyse the radiographic and histopathological features of ameloblastoma involving the mandible. Materials and methods: This was a retrospective, descriptive study of all histopathologically diagnosed ameloblastoma of the mandible over a period of 45 years. Patient demographics, radiographic and histopathological features were recorded and compared to previous studies. Results: A total of 148 lesions were included. The male to female ratio was nearly equal (1.05:1). The majority of patients were below 50 years of age (83.77%) and were black African (58.8%). The posterior region was the most affected site with majority of lesions presenting with multilocular appearance (68.24%) and root resorption (66.38%). Histologically, conventional ameloblastoma was the most common variant (48.65%). Conclusions: Mandibular ameloblastoma had a higher predilection for black African patients with higher prevalence of mixed density lesions when compared to previous studies. The size of lesions in this sample was considerably larger than those reported in previous studies. In addition, lesions in this sample also exhibited marked cortical expansion as well as root resorption.